Electoral competition and endogenous barriers to entry - Drometer, Marcus; Rincke, Johannes (European Journal of Political Economy, 2014)
As institutions matter for political and economic outcomes, they are (at least partly) shaped by the interests of political agents acting under these limitations. However, empirical evidence documenting such endogenous change of institutions is scarce. We address the issue by examining the link between the degree of electoral competition and the design of ballot access restrictions in the United States. Exploiting exogenous variation in electoral competition at the state level induced by the federal Voting Rights Act of 1965, our main finding is that ballot access rules have been systematically tightened in response to stronger electoral competition.
WiSo-Import:2015-03-26:5267
Keywords: political institutions; electoral competition; ballot access